Landscape character assessment as a tool for landscape planning / Mohd Zulhaili Teh - Teh, Mohd Zulhaili (2013)
Landscape is an important national resource which includes outstanding natural and cultural heritage. Landscape widely appreciated through aesthetic beauty and its important contribution to regional identity and sense of place. Landscape Character Assessment (LCA) is a tool used to evaluate landscape character in many developed countries that started in England and Scotland. Landscape character assessment can make a valuable contribution to the formation of planning policies, to the allocation of land for development and to development control activities. By investigating two successful Landscape Character Assessment model, this study attempt to explore the applicability of Landscape Character Assessment framework in Malaysia influences the process of planning, designing and managing of the landscape for sustainable future. Geographical Information System (GIS) application is used extensively to support evidence base Landscape Character Assessment for identification and classification of landscape character types and character areas in the state of Selangor as case study. The process of desk study validated by field survey and stakeholders input to provide framework for a fundamental structure of classifying the landscape character. The findings of desk study is validated by field work (ground thruthing) to shed information on landscape character types and landscape character areas currently exist in the study area. The information on the phenomenon of landscape described by the descriptive feature and the landscape character strength is assessed by the subjective aesthetic valuation in the interpretive process to evaluate the quality of the landscape character. The final result is the proposed alternatives management in term of conservation, preservation, enhancement and rehabilitation of landscape character area which will contribute to the decision making process in planning, design and management of the landscape resources in Malaysia.